Predicting the Tensile Properties of Recycled Polypropylene (r-PP)/Mengkuang Leaf Fibre (MLF) Composite using Mathematical Modelling - Karthegesu, Shamni (IRC, 2020)
Mathematical modelling has long been applied to predict the tensile properties of fibre-reinforced composites due to its ability to save time and cost when compared to experimental work. In this research, the natural fibres that were studied were obtained from mengkuang leaves due to its abundance and promising properties shown in previous research. It is also necessary to conduct a study regarding the application of mathematical modelling for natural fibres since it is not widely researched upon. Hence, the aims of this study were to predict the tensile properties of r-PP/MLF composites using mathematical models and to validate the results obtained from the calculations with previous experimental results. The material used in this study were r-PP and MLF with a composition of 60 wt.% and 40 wt.% respectively, while the results were compared to results obtained experimentally from a study published by M. Z. Abdullah and N. H. Che Aslan, titled ‘Performance Evaluation of Composite from Recycled Polypropylene Reinforced with Mengkuang Leaf Fiber’.